Com amor, uma análise sistêmico-funcional de cartas - Fachim, Graziela (2024)
The present study aims to investigate the representation of love through the lexical-grammatical and semantic-discursive choices employed in love letters from national and international contemporary literary authors. For this purpose, the theoretical principles of Systemic Functional Linguistics were considered, specifically the transitivity system (HALLIDAY; MATTHIESSEN, 2004), as well as the Appraisal system (MARTIN; WHITE, 2005), in association with psychology (PLUTCHIK, 1982) and sociology (BAUMAN, 2004; 2007). The research corpus consisted of 25 love letters written by national and international literary authors, available in the collection "Carta para você: Declarações de amor em tempos modernos" (KNELMAN; PORTER, 2009). Initially, the letters were analyzed according to the transitivity system, allowing the identification of how authors organize and construct meanings through language as a means of representing their experiences. In a second phase, the letters were analyzed according to the attitude subsystem, highlighting their evaluations and conceptions of this sentiment. Finally, the component aspects of love were highlighted, along with a symbolic representation, as evidenced by linguistic analyses. As a result, eight main components were identified: joy/happiness, trust/security, solidity, complexity, omnipresence, influence, emotion, and behavior. The combination of all these components resulted in their symbolic representation, comparable to a diamond.